The GLUT9 gene is associated with serum uric acid levels in Sardinia and Chianti cohorts. - Siguang Li; Serena Sanna; Andrea Maschio; Fabio Busonero; Gianluca Usala; Antonella Mulas; Sandra Lai; Mariano Dei; Marco Orrù; Giuseppe Albai; Stefania Bandinelli; David Schlessinger; et al. (PLoS Genetics)
High serum uric acid levels elevate pro-inflammatory-state gout crystal arthropathy and place individuals at high risk for cardiovascular morbidity and mortality. Genome-wide scans in the genetically isolated Sardinian population identified variants associated with serum uric acid levels as a quantitative trait. They mapped within GLUT9, a Chromosome 4 glucose transporter gene predominantly expressed in liver and kidney. SNP rs6855911 showed the strongest association (p = 1.84 x 10(-16)), along with eight others (p = 7.75 x 10(-16) to 6.05 x 10(-11)). Individuals homozygous for the rare allele of rs6855911 (minor allele frequency = 0.26) had 0.6 mg/dl less uric acid than those homozygous for the common allele; the results were replicated in an unrelated cohort from Tuscany. Our results suggest that polymorphisms in GLUT9 could affect glucose metabolism and uric acid synthesis and/or renal reabsorption, influencing serum uric acid levels over a wide range of values.